Mechanical and Chemical Characterization of a TiC/C System Synthesized Using a Focus Plasma Arc - Mahmoodian, Reza; Hamdi, M.; Hassan, M. A.; Akbari, Abolghasem (Public Library of Science, 2015)
Titanium carbide-graphite (TiC/C) composite was successfully synthesized from Ti and C starting elemental powders using self-propagating high-temperature synthesis technique in an ultra-high plasma inter medium in a single stage. The TiC was exposed to a high-temperature inert medium to allow recrystallization. The product was then characterized using field emission scanning electron microscopy (FESEM) coupled with energy dispersive X-ray analysis (EDX), X-ray diffraction (XRD), Rietveld refinement, nanoindentation, and micro-hardness to determine the product’s properties. The recorded micro-hardness of the product was 3660 HV, which is a 14% enhancement and makes is comparable to TiC materials.